A Mitochondrial Autonomously Replicating Sequence from Pichia pastoris for Uniform High Level Recombinant Protein Production - Schwarzhans, Jan-Philipp; Luttermann, Tobias; Wibberg, Daniel; Winkler, Anika; Hübner, Wolfgang; Huser, Thomas; Kalinowski, Jörn; Friehs, Karl (Frontiers in Microbiology, 2017)
Pichia pastoris is a non-conventional methylotrophic yeast that is widely used for recombinant protein production, typically by stably integrating the target gene into the genome as part of an expression cassette. However, the comparatively high clonal variability associated with this approach usually necessitates a time intense screening step in order to find strains with the desired productivity. Some of the factors causing this clonal variability can be overcome using episomal vectors containing an autonomously replicating sequence (ARS). Here, we report on the discovery, characterization, and application of a fragment of mitochondrial DNA from P. pastoris for use as an ARS. First encountered as an off-target event in an experiment aiming for genomic integration, the newly created circular plasmid named “pMito” consists of the expression cassette and a fragment of mitochondrial DNA. Multiple matches to known ARS consensus sequence motifs, but no exact match to known chromosomal ARS from P. pastoris were detected on the fragment, indicating the presence of a novel ARS element. Different variants of pMito were successfully used for transformation and their productivity characteristics were assayed. All analyzed clones displayed a highly uniform expression level, exceeding by up to fourfold that of a reference with a single copy integrated in its genome. Expressed GFP could be localized exclusively to the cytoplasm via super-resolution fluorescence microscopy, indicating that pMito is present in the nucleus. While expression levels were homogenous among pMito clones, an apparent upper limit of expression was visible that could not be explained based on the gene dosage. Further investigation is necessary to fully understand the bottle-neck hindering this and other ARS vectors in P. pastoris from reaching their full capability. Lastly, we could demonstrate that the mitochondrial ARS from P. pastoris is also suitable for episomal vector transformation in Saccharomyces cerevisiae, widening the potential for biotechnological application. pMito displayed strong potential to reduce clonal variability in experiments targeting recombinant protein production. These findings also showcase the as of yet largely untapped potential of mitochondrial ARS from different yeasts for biotechnological applications.